Development of a dual immunochromatographic test strip to detect E2 and Erns antibodies against classical swine fever - Huynh, Loc Tan; Sohn, Eun-Ju; Park, Youngmin; Kim, Juhun; Shimoda, Tomohiko; Hiono, Takahiro; Isoda, Norikazu; Hong, Sung-Hee; Lee, Ha-Na; Sakoda, Yoshihiro (Frontiers in Microbiology, 2024)
Background: It is essential to consider a practical antibody test to successfully implement marker vaccines and validate vaccination efficacy against classical swine fever virus (CSFV). The test should include a serological antibody assay, combined with a tool for differentiating infected from vaccinated animals (DIVA). The immunochromatographic test strip (ICS) has been exclusively designed for detecting CSFV E2 antibodies while lacking in detecting Erns antibodies, which can be employed and satisfy DIVA strategy. This study developed a novel ICS for detecting CSFV E2/Erns dual-antibody. The effectiveness of ICS in evaluating the DIVA capability of two novel chimeric vaccine candidates was assessed. Methods: Recombinant E2 or Erns protein was transiently expressed in the plant Nicotiana benthamiana using Agrobacterium tumefaciens. ICS was subsequently assembled, and goat anti-rabbit IgG and recombinant CSFV E2 or Erns protein were plated onto the nitrocellulose membrane as control and test lines, respectively. ICS sensitivity and specificity were evaluated using sera with different neutralizing antibody titers or positive for antibodies against CSFV and other pestiviruses. Coincidence rates for detecting E2 and Erns antibodies between ICS and commercial enzyme-linked immunosorbent assay (ELISA) kits were also computed. ICS performance for DIVA capability was evaluated using sera from pigs vaccinated with conventional vaccine or chimeric vaccine candidates. Results: E2 and Erns proteins were successfully expressed in N. benthamiana-produced recombinant proteins. ICS demonstrated high sensitivity in identifying CSFV E2 and Erns antibodies, even at low neutralizing antibody titers. No cross-reactivity with antibodies from other pestiviruses was confirmed using ICS. There were high agreement rates of 93.0% and 96.5% between ICS and two commercial ELISA kits for E2 antibody testing. ICS also achieved strong coincidence rates of 92.9% and 89.3% with two ELISA kits for Erns antibody detection. ICS confirmed the absence of CSFV Erns-specific antibodies in sera from pigs vaccinated with chimeric vaccine candidates. Conclusions: E2 and Erns proteins derived from the plant showed great potential and can be used to engineer a CSFV E2/Erns dual-antibody ICS. ICS was also highly sensitive and specific for detecting CSFV E2 and Erns antibodies. Significantly, ICS can fulfill the DIVA concept by incorporating chimeric vaccine candidates.